Gas‐Phase Polyethylene Reactors—A Critical Review of Modeling Approaches. Issue 3 (1st April 2021) - Alves, Rita Ferreira; Casalini, Tommaso; Storti, Giuseppe; McKenna, Timothy F. L.
Abstract: Different approaches to modeling the gas phase polymerization of ethylene that have been considered in the literature are reviewed. It is shown that while simple, well‐mixed models can give an adequate representation of the average performance of a given polymerization reactor, they do not allow one to analyze certain modeling problems such as the existence of temperature gradients or particle segregation, nor can they be used to treat operational modes such as condensed cooling where there can be up to three different phases in different parts of the reactor. For this, more complex models are required. These can take the form of compartmentalized models or even models based on computation fluid dynamics. However, long computational times can be required to fully exploit these models. Furthermore, significant progress needs to be made if one needs to address important phenomena such as agglomeration or particle attrition during polymerization. Abstract : The task of modeling the polymerization of olefins in fluidized bed reactors can be quite daunting, depending on the level of complexity one requires, and on the accuracy of the kinetic, transport, and thermodynamic models available. The strengths and weaknesses of the different approaches are reviewed with a view of guiding the reader in the most appropriate choice.